Pituitary deficiency following aneurysmal subarachnoid haemorrhage. Issue 8 (21st July 2003) - Kreitschmann-Andermahr, I; Hoff, C; Niggemeier, S; Pruemper, S; Bruegmann, M; Kunz, D; Matern, S; Gilsbach, J M
Abstract : Objective: To investigate the incidence and severity of pituitary insufficiency after aneurysmal subarachnoid haemorrhage. Methods: Pituitary function was tested in a series of patients more than 12 months but less than 60 months after aneurysmal subarachnoid haemorrhage using a combined TRH-LHRH-arginine test and the insulin tolerance test, to elucidate possible deficits in the gonadotrophic, somatotrophic, thyreotrophic, and corticotrophic hormonal axes. Results: Of 21 patients screened, nine (43%) showed deficiencies of at least one pituitary hormone axis. Four patients had corticotrophin deficiency, one had partial growth hormone deficiency, two had severe growth hormone deficiency, and two had severe growth hormone deficiency plus corticotrophin deficiency. Conclusions: Persistent pituitary dysfunction may be more common after aneurysmal subarachnoid haemorrhage than has so far been recognised and warrants further investigation, given the possibility that some health and neurobehavioural problems in these patients could result from hormone deficiency.